(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Sunshine Gold, a crucial element, namely vitamin D, is essential for maintaining calcium homeostasis and promoting bone mineralization. Its deficiency has become a global health issue, particularly concerning in our country, affecting people from all socioeconomic and geographic backgrounds, especially females and children. Methods: 111 blood samples were investigated in the In-vitro Division of the Institute of Nuclear Medicine and Allied Sciences (INMAS) in Mohakhali, Dhaka from January to December 2024. Demographic and socio-economic impacts on vitamin D levels and their probable reasons are investigated through several statistical and mathematical analytics. Results: About 75.67% of people are deficient in vitamin D (<20 ng/mL). Deficiency was noted in 61.90% of females (mean ± S.D.) 11.21 ± 4.50 ng/mL and 11.98 ± 3.43 ng/mL in males, indicating higher levels of vitamin D in males. Approximately 60.00% of participants aged 19-40 years had a deficiency with 11.29 ± 3.80 ng/mL. Seasonal studies showed higher vitamin D levels in summer due to increased sun exposure. Housewives exhibited notable deficiencies with an average level of 9.38 ± 4.50 ng/mL, comprising 19.05% of the deficient group. People from lower socioeconomic classes had longer sun exposure, resulting in higher vitamin D concentrations. Conclusion: It is a pressing need for comprehensive public health interventions to address the significant prevalence of vitamin D deficiency among Bangladeshis. Increasing public awareness about the levels of vitamin D and its interrelations to sun exposure, boosting dietary sources of vitamin D, and considering food fortification initiatives are some possible strategies. Bangladesh J. Nuclear Med. 28(1): 142-148, 2025